Principles of geotechnical engineering - Das, Braja M. (Cengage, 2022)
"Provide a valuable overview of soil properties and mechanics together with coverage of field practices and basic engineering procedures with Das and Sobhan, PRINCIPLES OF GEOTECHNICAL ENGINEERING, SI EDITION, 9E. This market-leading introduction to geotechnical engineering is ideal for the foundational course taken by most civil engineering students. This book provides the important background knowledge students need to support study in later design-oriented courses and in professional practice. The authors ensure a practical and application-oriented approach to the subject by incorporating a wealth of comprehensive discussions and detailed explanations. Find more figures and worked-out problems than any other book for the course to help ensure student understanding."